Logic and automata : history and perspectives - Flum, Jörg; Grädel, Erich, 1958-; Wilke, Thomas, 1965- (Texts in logic and games, 2008)
This collection of papers deal with challenges in disciplines such as complexity theory, games, algorithms and semi group theory and discuss current chellenges in this field.